CONTRIBUTION OF SOYA TEMPE (Glycine max) INDUSTRIAL INCOME OF HOUSEHOLD SCALE TO CRAFTSHIP HOUSEHOLD INCOME IN SOYA TEMPE (Glycine max) in IMOGIRI DISTRICT, BANTUL REGENCY - Risky Amelia; Ari Astuti (Fakultas Pertanian UST, 2018)
The aims research to contribution of soya tempe industry income to household income of soya tempe craftsmen in Imogiri Sub-district, Bantul District, the purpose of this research are to knowing the production cost and income from soya tempe industry of household scale and to contribution of soya tempe industry income to household income of soybean tempe craftsman in Imogiri district, Bantul regency in July 2017. The research method used is descriptive. The method of determining the location was done intentionally in Imogiri District. Determination of the number of samples is done proportionally. While the sampling method using random sampling with a sample of 32 people.Data analysis method used is the method of income analysis and T-test.The analysis result shows that the average of soybean tempe industry income obtained by the soybean tempe craftsmen in one month is Rp 1.351.435,00, meanwhile the income outside of tempe industry business Rp 990.841,00 and the total income of soybean craftsman in one month Rp 2.342.276,00 so it can be seen that the income of soya tempe industry has contributed 57.7% to household income of soybean tempe craftsmen in Imogiri District. Test result t-test obtained t count = 2.212 and t table = 2.03951, so t count is greater than t table with 95% confidence level, then Ha accepted and rejected Ho. Thus, soybean tempe industry income contributes â‰¥50% to household income.